AB0687 Association between golimumab tapering strategy and drug serum levels in spa-paz spondiloarthritis cohort. (15th June 2017) - Redondo, C; Martínez, A; Plasencia, C; Navarro-Compán, V; Nuño, L; Peiteado, D; Villalba, A; Jochems, A; Pascual-Salcedo, D; Balsa, A
Abstract : Background: Golimumab (Glm) is a tumour necrosis factor (TNF) inhibitor used as Spondiloarthritis (SpA) treatment. There is more and more evidence of tapering therapies used in maintained low disease activity patients, avoiding overtreatments and adverse effects. Up to now, there are no studies concerning SpA patients with Glm tapering therapy and serum drug levels measured prior to tapering strategy. Objectives: To analyze clinical and analytical course of SpA patients with Glm interval prolongation in SpA-Paz cohort. Associate pre-tapering Glm serum levels with flare occurrence along tapering treatment. Methods: Observational prospective SpA-Paz cohort study of 22 patients treated with Glm that remained with low disease activity, so they started tapering strategy (Tap-S). We measured clinical activity with ASDAS and ΔASDAS at baseline, pre-tapering visit (v-pre)and at 6, 12, 18 and 24 months after tapering starting (v-end). All of them had a clinically important improvement determined as ΔASDAS≥1'1. We registered flares, defined as clinical worsening based on patient anamnesis and physical examination and on diverse activity indexes made from the beginning until the last visit. Drug serum levels in v-pre were measured by ELISA and classified following optimal concentration previously defined in our laboratory: <0'7 mg/L, 0'7–1'4 mg/L, >1'4 mg/L. We used the software Graph-Pad Prism 6 for statistical analysis. Results: 22 of 79 patients from our cohort (28%) initiated Tap-S. The age range was between 25 and 70 years, 73% men and 27% women. 52% were non-smokers. 5 patients (23%) received another antiTNF drug previously (4 Infliximab, 1 Etanercept). All of them had a 6 months visit prior to tapering, 18 patients had 12 months visit, 8 had 18 months visit and 5 had 24 months visit. ASDAS and ΔASDAS were similar in v-pre and v-end (ASDAS: 1'3±0'4 v-pre vs 1'2±0'7 v-fin, p=0'3; ΔASDAS: 2'3±0'7 v-pre vs 2'4±0'9 v-end, p=0'6). 13 patients (59%) had 1 or 2 flares along tapering therapy. The occurrence of flare average was 14 months. In all the patients with flares, disease activity was controlled returning to previous tapering dose (4/13, 31%), to monthly schedule (6/13, 46%) or remaining tapering dose with symptomatic treatment adjustments (3/13, 23%). None of them discontinued the treatment. At v-end, ASDAS and ΔASDAS were similar between patients with and without flares along Tap-S (ASDAS v-end: 1±0'7 in patients without flares vs 1'3±0'7 in patients with flares, p=0'4, ΔASDAS v-fin: 2'7±0'7 in patients without flares vs 2'2±1 in patients with flares, p=0'3). All the patients (4/4, 100%) that were under optimal drug concentration (<0'7mg/L) had at least one flare along Tap-S; however, only 23% (3/9) of those who were in optimal drug concentration in v-pre (0'7–1'4 mg/L) had flares. Conclusions: The tapering strategy in our SpA cohort treated with Glm results in similar disease activity control after 24 months of monitoring. The activity disease in patients with flares was controlled with symptomatic or biologic treatment adjustments avoiding therapy discontinuation. Flares incidence was more frequent in patients under optimal drug concentration in v-pre. Disclosure of Interest: None declared